CONSUMERS‘ SATISFACTION TOWARDS THE USAGE OF CHINESE TRADITIONAL CULTURAL ELEMENTS IN FURNITURE PRODUCTS：A QUALITATIVE RESEARCH APPROACH - Guo , Shuang; Mohamad, Darliana; Hapiz, Hana Yazmeen (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
This study tries to find out consumers’ satisfaction towards the usage of Chinese traditional cultural elements in furniture elements. A qualitative method is adopted in this study to investigate 10 consumers’ perspectives. 10 consumers are all form Nanjing city in China. The results shows that all the interviewed consumers know the existence of the furniture products integrating with Chinese traditional cultural elements. What’s more, they are not satisfied with the current situation of the usage Chinese traditional cultural elements in furniture products. Most consumers point out that the cedar and the plum are the favorite elements that they prefer to use in the furniture products. The usage of consumers’ favorite elements will increase consumers intension of purchase, but the price and functional attributes should also be taken into full consideration. This study has a strong practical significance for furniture designer and workers of cultural and creative products.